2021
DOI: 10.5812/aapm.108915
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Efficacy of Dexmedetomidine Versus Labetalol in Providing Controlled Hypotension in Functional Endoscopic Sinus Surgery

Abstract: Background: Functional endoscopic sinus surgery (FESS) is a surgical intervention for sinus diseases. Bleeding is a common concern during FESS. Hemodynamic stability and quality surgical field visibility help to achieve the best outcomes. Objectives: The present study primarily intended to compare the effectiveness of dexmedetomidine versus labetalol in providing controlled hypotension during FESS and then to assess the quality of the surgical field. Methods: The current research was conducted as a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…For 5) noticed a significant reduction of intraoperative -BIS guided-fentanyl and propofol utilization in patients undergoing cerebellopontine angle surgeries. Also, the same finding is consistent with studies done on other types of surgeries (23,24). In dis-concordance to our results, Sriganesh and their colleagues (6,7) demonstrated that a dexmedetomidine infusion of 0.5 µg/kg/h without loading dose was not superior to fentanyl.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For 5) noticed a significant reduction of intraoperative -BIS guided-fentanyl and propofol utilization in patients undergoing cerebellopontine angle surgeries. Also, the same finding is consistent with studies done on other types of surgeries (23,24). In dis-concordance to our results, Sriganesh and their colleagues (6,7) demonstrated that a dexmedetomidine infusion of 0.5 µg/kg/h without loading dose was not superior to fentanyl.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Chakrabati et al ( 5 ) noticed a significant reduction of intraoperative -BIS guided- fentanyl and propofol utilization in patients undergoing cerebellopontine angle surgeries. Also, the same finding is consistent with studies done on other types of surgeries ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…tion, dexmedetomidine has also been used for sedation during awake fibreoptic intubation (16), reducing emergence delirium in children for strabismus surgery (17), premedicating children undergoing dental procedures (18), reducing the hemodynamic changes during elective colonoscopy (19), improving post-cesarean analgesia (20), sedating patients for closed reduction of nasal fractures (21), providing controlled hypotension during functional endoscopic sinus surgery (22), and reducing postoperative cognitive dysfunction (POCD) after middle ear surgery under hypotensive technique (23). Dexmedetomidine has also been used more importantly as an adjuvant to improve chronic and neuropathic pain and prolong the effects of chronic pain procedures (24).…”
Section: Contextmentioning
confidence: 99%
“…Different types of drugs have been investigated to provide "controlled hypotension" during surgeries, including opioids (9)(10)(11)(12), beta-blockers (13,14), vasodilators (15,16), and α2-adrenoreceptor agonists (9,11,12,14,17). Dexmedetomidine, an α2-agonist, has been used as a sedative (18)(19)(20), anxiolytic (21), and hypotensive (22,23) agent for anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in cardiac output is due to a negative chronotropic effect of dexmedetomidine, and the systolic and diastolic function is not impaired (34). The hypotensive and heart ratereducing properties of this agent make it a reasonable choice for procedures requiring "controlled hypotension", and it has been demonstrated to have favorable effects compared to other drugs in this regard (9,11,12,14,17). Furthermore, the administration of dexmedetomidine during operation is associated with a decrease in the incidence of postoperative shivering, nausea, vomiting, delirium, and postoperative cognitive dysfunction (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%